EFFECT OF ANTIEPILEPTIC DRUG THERAPY ON THYROID FUNCTION AND THYROID VOLUME IN CHILDREN WITH SEIZURE DISORDERS: A PROSPECTIVE OBSERVATIONAL STUDY - BODHISATYA DAS; WASIM AKRAM; MAHAPRASAD PAL; PRANAB DAS (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The objective of the study is to evaluate the effect of antiepileptic drug (AED) therapy on thyroid function parameters and thyroid volume in children aged 2–12 years with seizure disorders. Methods: This prospective observational study included 45 children aged 2–12 years with seizure disorders receiving antiepileptic therapy and followed for 6 months. Serum thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), and thyroid volume by ultrasonography were assessed at baseline, 3 months, and 6 months. Participants received monotherapy or polytherapy, predominantly sodium valproate, phenytoin, and levetiracetam. Data were analyzed using repeated measures analysis of variance and the Mann–Whitney U test (p<0.05 considered significant). Results: The mean age of participants was 7.29±2.69 years. On pooled analysis, mean TSH levels showed a mild, non-significant increase over time (p=0.40), while FT3 and FT4 levels remained stable. However, children receiving sodium valproate demonstrated a statistically significant rise in mean TSH from 3.07±1.45 to 3.24±1.56 mIU/L at 6 months (p=0.032), with normal FT3 and FT4 levels. Subgroup analysis confirmed that this significant change was observed only with sodium valproate (p=0.032). Thyroid volume showed a marginal, non-significant increase during follow-up (p=0.15), with no significant difference between monotherapy and polytherapy groups. Conclusion: Sodium valproate therapy in children is associated with a significant rise in TSH levels suggestive of subclinical hypothyroidism. Periodic thyroid function monitoring every 6–12 months is advisable in children receiving long-term sodium valproate therapy.